2002
DOI: 10.1093/hmg/11.17.2037
|View full text |Cite
|
Sign up to set email alerts
|

hnRNP-G promotes exon 7 inclusion of survival motor neuron (SMN) via direct interaction with Htra2-beta1

Abstract: Proximal spinal muscular atrophy (SMA) is a common motor neuron disease caused by homozygous loss of the survival motor neuron gene (SMN1). SMN2, a nearly identical copy of the gene and present in all SMA patients, fails to provide protection from SMA, due to the disruption of an exonic splicing enhancer (ESE) by a single translationally silent nucleotide exchange, which causes alternative splicing of SMN2 exon 7. Identification of splicing factors that stimulate exon 7 inclusion and thereby produce sufficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
142
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(147 citation statements)
references
References 44 publications
5
142
0
Order By: Relevance
“…Most studied among them is the SR-like protein Tra2-␤1 that binds to a purine-rich ESE in the middle of exon 7 (18). Elevated expression of Tra2-␤1 (18) or its associated proteins hnRNP G (19) and Srp30c (59) has been shown to promote exon 7 inclusion in SMN2. A recent study in which increased expression of the STAR (signal transduction and activation of RNA) family of proteins promoted exclusion of exon 7 suggests tissue-specific regulation (55).…”
mentioning
confidence: 99%
“…Most studied among them is the SR-like protein Tra2-␤1 that binds to a purine-rich ESE in the middle of exon 7 (18). Elevated expression of Tra2-␤1 (18) or its associated proteins hnRNP G (19) and Srp30c (59) has been shown to promote exon 7 inclusion in SMN2. A recent study in which increased expression of the STAR (signal transduction and activation of RNA) family of proteins promoted exclusion of exon 7 suggests tissue-specific regulation (55).…”
mentioning
confidence: 99%
“…Consistent with this, RBMX has been identified as a component of the spliceosome [7]. RBMX has been shown to interact with Tra2β, a SR-rich splicing activator, as well as the SR-like protein Htra2-β1 [8,9]. In contrast, RBMX and Tra2β have been shown to have opposite effects on exon splicing, with both being capable of acting as activators or repressors [10].…”
Section: Discussionmentioning
confidence: 74%
“…RBMX, which contains a RNA-binding domain, binds RNA non-specifically [8,10]. We showed that RNase treatment markedly increased the association between endogenous RBMX and ARTS-1, whereas RNase inhibitors had no effect.…”
Section: Discussionmentioning
confidence: 78%
“…The only functionally relevant difference between the SMN1 and SMN2 genes identified to date is a C ! T transition at position þ6 of exon 7 of SMN2 [Monani et al, 1999;Lorson et al, 1999] which disrupts interactions of the pre-mRNA with splicing enhancer and silencer proteins such that SMN2 transcripts predominantly exclude exon 7 (SMND7) Cartegni and Krainer, 2002;Hofmann and Wirth, 2002;Kashima and Manley, 2003;Singh et al, 2006;Chen et al, 2008;Gladman and Chandler, 2009]. SMN2 genes do not produce sufficient full length SMN protein to prevent the onset of the disease but, on the other hand, because each SMN2 gene can produce a small amount of full length SMN transcripts, no patient is devoid of SMN protein and disease severity is dependent on the amount of residual SMN protein [reviewed in Burghes and Beattie, 2009].…”
Section: Introductionmentioning
confidence: 99%